Impact of chronic low to moderate alcohol consumption on blood lipid and heart energy profile in acetaldehyde dehydrogenase 2-deficient mice - FAN Fan; CAO Quan; WANG Cong; MA Xin; SHEN Cheng; LIU Xiang-wei; BU Li-ping; ZOU Yun-zeng; HU Kai; SUN Ai-jun; GE Jun-bo (Acta Pharmacologica Sinica, 2016)
Fan FAN1, #, Quan CAO1, #, Cong WANG1, #, Xin MA1, 2, Cheng SHEN1, Xiang-wei LIU1, Li-ping BU1, Yun-zeng ZOU1, 2, Kai HU1, Ai-jun SUN1, 2, *, Jun-bo GE1, 2, * 1Shanghai Institute of Cardiovascular Diseases, Zhongshan Hospital, Fudan University, Shanghai 200032, China; 2Institute of Biomedical Science, Fudan University, Shanghai 200032, China Aim: To investigate the roles of acetaldehyde dehydrogenase 2 (ALDH2), the key enzyme of ethanol metabolism, in chronic low to moderate alcohol consumption-induced heart protective effects in mice. Methods: Twenty-one male wild-type (WT) or ALDH2-knockout (KO) mice were used in this study. In each genotype, 14 animals received alcohol (2.5%, 5% and 10% in week 1–3, respectively, and 18% in week 4–7), and 7 received water for 7 weeks. After the treatments, survival rate and general characteristics of the animals were evaluated. Serum ethanol and acetaldehyde levels and blood lipids were measured. Metabolomics was used to characterize the heart and serum metabolism profiles. Results: Chronic alcohol intake decreased the survival rate of KO mice by 50%, and significantly decreased their body weight, but did not affect those of WT mice. Chronic alcohol intake significantly increased the serum ethanol levels in both WT and KO mice, but KO mice had significantly higher serum acetaldehyde levels than WT mice. Chronic alcohol intake significantly increased the serum HDL cholesterol levels in WT mice, and did not change the serum HDL cholesterol levels in KO mice. After chronic alcohol intake, WT and KO mice showed differential heart and serum metabolism profiles, including the 3 main energy substrate types (lipids, glucose and amino acids) and three carboxylic acid cycles. Conclusion: Low to moderate alcohol consumption increases HDL cholesterol levels and improves heart energy metabolism profile in WT mice but not in ALDH2-KO mice. Thus, preserved ALDH2 function is essential for the protective effect of low to moderate alcohol on the cardiovascular system. Keywords: alcohol; chronic alcohol intake; cardiovascular protection; acetaldehyde dehydrogenase 2; HDL cholesterol; heart energy profile; metabolomics This work was supported by the National Basic Research Program of China (No 2011CB503905), National Natural Science Foundation of China (No 30971250, 81300096), and Program for New Century Excellent Talents in University (NCET). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail jbge@zs-hospital.sh.cn (Jun-bo GE); sun.aijun@zs-hospital.sh.cn (Ai-jun SUN). Received 2014-02-17 Accepted 2014-05-04